Effect of Varying Geometrical Parameters of Trapezoidal Corrugated-Core Sandwich Structure - N. Z. M., Zaid; M. R. M., Rejab; A. F., Jusoh; Bachtiar, Dandi; Siregar, J. P. (EDP Sciences, 2017)
Sandwich structure is an attractive alternative that increasingly used in the transportation and aerospace industry. Corrugated-core with trapezoidal shape allows enhancing the damage resistance to the sandwich structure, but on the other hand, it changes the structural response of the sandwich structure. The aim of this paper is to study the effect of varying geometrical parameters of trapezoidal corrugated-core sandwich structure under compression loading. The corrugated-core specimen was fabricated using press technique, following the shape of trapezoidal shape. Two different materials were used in the study, glass fibre reinforced plastic (GFRP) and carbon fibre reinforced plastic (CFRP). The result shows that the mechanical properties of the core in compression loading are sensitive to the variation of a number of unit cells and the core thickness.